CONTEXTUAL TEACHING-LEARNING MODEL WITH TEAMS GAMES TOURNAMENT TECHNIQUE TO INCREASE MOTIVATION AND OUTCOMES OF IPS LEARNING FOR SIXTH-GRADE STUDENTS SD NEGERI 3 KLOPOSAWIT - Teguh Sucipto (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2022)
The aims of this study: (1) to apply the Contextual Teaching Learning TGT technique to social studies learning, (2) to improve social studies learning outcomes for sixth-grade students at SD Negeri 3 Kloposawit, (3) to increase social studies learning motivation for sixth-grade students at SD Negeri 3 Kloposawit. The type of research is Classroom Action Research (CAR) by adopting the research model of Kemmis and Mc Taggart. The research subjects were 14 sixth-grade students at SD Negeri 3 Kloposawit consisting of 10 male and four female students. Data collection techniques using test and observation techniques. Analysis of research data using quantitative descriptive analysis techniques. The results of the data analysis prove that using Contextual Teaching Learning with the TGT technique can increase motivation to learn social studies material about natural events that occurred in Indonesia and neighboring countries for sixth-grade students at SD Negeri 3 Kloposawit. Data on student learning outcomes prior to treatment, cycle I, and cycle II showed a positive trend, from 5 students (35.71%) who had scores above the KKM to 9 students (64.29%) and 14 students (100%). While the data on the percentage of students' learning motivation in the pre-cycle, cycle I, and cycle II were 21.43%, 57.14%, and 92.86%, respectively. Keywords: Contextual Teaching Learning, IPS Learning, Learning Outcomes, Learning Motivation